Desenvolvimento de um sistema de microtomografia de raios X de baixo custo para amostras de pequenas dimensões e baixas densidades - Vilar, Artur Batista (2017)
In this thesis, the development of a relatively inexpensive microtomographic system for the analysis of samples of small dimensions and low densities is presented. A flat panel detector originally developed for dental applications was used. The characterization process that allowed its implementation in a microtomographic system is detailed in the work. A study of the linear and volumetric magnifications of the system was carried out, allowing qualitative analysis to be obtained quantitative information of the sample investigated. The electromechanical control of object rotation and radiation exposure control was developed using the Arduino platform. A set of computational tools allowed the management of data acquisition and control of the entire system. As a final result, a functional system capable of implementing the whole microtomographic process is presented, from the acquisition of the two-dimensional projections to the three-dimensional visualization of the external and internal structures obtained in the microtomographic reconstruction process. Finally, results are obtained with samples such as a PVC tube, a small frog, a gecko and a human tooth where it was possible to visualize in detail its main characteristics and internal compositions.